2017
DOI: 10.13053/cys-21-2-2734
|View full text |Cite
|
Sign up to set email alerts
|

Word Embeddings for User Profiling in Online Social Networks

Abstract: User profiling in social networks can be significantly augmented by using available full-text items such as posts or statuses and ratings (in the form of likes) that users give them. In this work, we apply modern natural language processing techniques based on word embeddings to several problems related to user profiling in social networks. First, we present an approach to create user profiles that measure a user's interest in various topics mined from the full texts of the items. As a result, we get a user pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…As found in [3], for predicting demographic data with Word2Vec-based user profiles, models trained with a custom text dataset yield better results than those using a large general language corpus. Considering also the dynamic nature of news content and changing user interests, we verify this claim and use a Word2Vec model trained on a corpora consisting of Polish Wikipedia and National Corpus of Polish Language NKJP [25] to compare with our models built on a much smaller custom corpus with the same model parameters.…”
Section: Data Descriptionmentioning
confidence: 64%
See 3 more Smart Citations
“…As found in [3], for predicting demographic data with Word2Vec-based user profiles, models trained with a custom text dataset yield better results than those using a large general language corpus. Considering also the dynamic nature of news content and changing user interests, we verify this claim and use a Word2Vec model trained on a corpora consisting of Polish Wikipedia and National Corpus of Polish Language NKJP [25] to compare with our models built on a much smaller custom corpus with the same model parameters.…”
Section: Data Descriptionmentioning
confidence: 64%
“…Among the frameworks applied to demography prediction, there are both topic modeling approaches and Word2Vec representations. Moreover, in [2,3], the authors use Word2Vec-based profiles from social media texts for predicting a user's age and recommendations. We also apply profiles based on Word2Vec word representations and compare their results with the topic modeling approach for predicting user gender.…”
Section: Demography Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there have been a few attempts to apply text embedding methods to represent content-based user profiles. In Musto et al (2016); Alekseev et al (2017); Misztal-Radecka (2018), Word2Vec is used to build content-based user profiles. It was observed that this approach gives comparable results to the standard collaborative filtering techniques, especially for sparse datasets.…”
Section: From Word Vectors To User Embeddingsmentioning
confidence: 99%